2018
DOI: 10.1590/1413-81232018233.09492016
|View full text |Cite
|
Sign up to set email alerts
|

Teores de mercúrio em cabelo e consumo de pescado de comunidades ribeirinhas na Amazônia brasileira, região do Tapajós

Abstract: Resumo Comunidades ribeirinhas estão expostas ao mercúrio devido à dieta composta por elevada ingestão de peixes. Com o objetivo de avaliar os níveis de exposição na região do Tapajós, identificando também a frequência de ingestão de pescado, realizou-se um estudo em adultos residentes nas comunidades ribeirinhas do município de Itaituba/PA. Foram coletadas amostras de cabelo para a determinação de mercúrio total e dados de frequência semanal de ingestão de peixes. A concentração média de mercúrio total variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…This study found that the frequency of fish consumption was associated exclusively with mercury levels in hair, which suggests that fish consumption is a good proxy for mercury exposure in this region. This was also evidenced by Costa Junior et al [29] in their study of the Pará region of Brazil and Santos et al in their research on an indigenous population in that country [30].…”
Section: Blood Mercury Levels After Exposuresupporting
confidence: 57%
“…This study found that the frequency of fish consumption was associated exclusively with mercury levels in hair, which suggests that fish consumption is a good proxy for mercury exposure in this region. This was also evidenced by Costa Junior et al [29] in their study of the Pará region of Brazil and Santos et al in their research on an indigenous population in that country [30].…”
Section: Blood Mercury Levels After Exposuresupporting
confidence: 57%
“…A região PAN-Amazônica compreende uma área total de 5,5 milhões de km A região amazônica se constitui no bioma com a maior biodiversidade de fauna e flora do mundo, o que desperta interesse de inúmeros países pela busca cientifica de identificar e caracterizar novas espécies de animais e plantas, sendo esta última para interesses farmacêuticos para uma ampla aplicação em processos terapêuticos que não possuem e/ou carece de formas de tratamento que leve tanto a cura, quanto o aumento da expectativa de vida da sociedade (CASTRO et al, 2016;JÚNIOR et al, 2018;PIMENTEL et al, 2019). Além disso, a presença de uma grande diversidade cultural em função de tribos indígenas, seringueiros, castanheiros, quebradores de coco de babaçu, ribeirinhos entre outras; se constitui em um patrimônio nacional e mundial (CORNETTA; RÊGO, 2021; DAMAS; BERTOLDO; COSTA, 2014;SÁ et al, 2016;SANTOS et al, 2003;TORREZANI et al, 2016).…”
Section: Região Pan-amazônicaunclassified
“…There is a worldwide concern with exposure to mercury, especially in riverine communities where high amounts of contaminated fish are consumed, as this chemical element has adverse health effects. And if women of reproductive age are contaminated, it can also affect reproduction (33)(34)(35)(36) . Studies point to possible problems related to reproduction: increased risk of reduced fertility, spontaneous abortion, congenital deficiencies and/or abnormalities (33)(34)(35) .…”
Section: Environmental Componentmentioning
confidence: 99%
“…Considering this problem, studies recommend monitoring the levels of mercury in riverine women of reproductive age, since children under 24 months of age, who still do not eat fish, already have concentrations of mercury above the safety level, suggesting intrauterine contamination and/or contamination by breast milk (19,26,(33)(34)(35)(36) .…”
Section: Environmental Componentmentioning
confidence: 99%